2.0 academic management: Reimagining departments and colleges for the 21st century. Issue 2 (19th September 2018) - Chu, Don
Abstract : Since Henry Ford's time, the world has changed. In the last 100 years, how much has changed in how colleges are run? When asked whether the current higher education system is preparing students for the future former Secretary of Labor Robert Reich and current professor of public policy at the University of California, Berkeley replied, "Absolutely not. I'm going to make a crass generalization about the current system of higher education in general, but I think it's accurate. It is still wedded to a 20th century model of education, which in turn comes to us from the 18th century."